1993
DOI: 10.1017/s0317167100048599
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Simple and Impaired Compound Movement After Infarction in the Territory of the Superior Cerebellar Artery

Abstract: ABSTRACT:A patient with an infarct in the distribution of the right superior cerebellar artery was studied with regard to his ability to make simple movements (visually triggered, self-terminated ballistic wrist movements), and compound movements (reaching to a visual target and precision pinch of a seen object). Movements on the right side of the body alone were affected. Control movements were made by the normal left upper extremity. Wrist movement on the right side was normal in reaction time, direction, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…In the Introduction, we have already discussed some evidence that cerebellar lesions in humans severely and specifically impair the timing of movements. This is consistent with the role of the cerebellum in the timed coordination of movements (Haggard et al, 1995;Goodkin, Keating, Martin, & Thach, 1993). In monkeys, lesions of the lateral cerebellar nuclei fail to reduce response times on the basis of information predicting either the timing or the location of stimuli (Nixon & Passingham, 1999).…”
Section: Cortico-cerebellar Loops: Motor Learning Timing and Predicsupporting
confidence: 83%
“…In the Introduction, we have already discussed some evidence that cerebellar lesions in humans severely and specifically impair the timing of movements. This is consistent with the role of the cerebellum in the timed coordination of movements (Haggard et al, 1995;Goodkin, Keating, Martin, & Thach, 1993). In monkeys, lesions of the lateral cerebellar nuclei fail to reduce response times on the basis of information predicting either the timing or the location of stimuli (Nixon & Passingham, 1999).…”
Section: Cortico-cerebellar Loops: Motor Learning Timing and Predicsupporting
confidence: 83%
“…Direction and gravity are two factors influencing the severity of these deficits [126]. Both movement initiation and termination are impaired.…”
Section: Dysfunction Of Voluntary Limb Movements In Cerebellar Patienmentioning
confidence: 99%
“…Studies of similar tasks in highly trained monkeys suggest that the cerebellum is likely to play a critical role in generating this response (3). In humans, cerebellar malfunction results in the loss of ability to anticipate and compensate for interaction torques that are generated in multijoint arm movements (31 ). Although the role of the cerebellar cortex in initial acquisition of the IM is unclear (32), it has been shown that within an hour after completion of motor learning, biochemical processes that are involved in the synaptic remodeling of Purkinje cells are initiated (33).…”
Section: Lmentioning
confidence: 99%